Exploring Employee Creativity Behaviours at Work: The Impact of Psychological, Organisational and Work Factors - Ghafoor, Azka (Auckland University of Technology, 2020)
Creativity is the crucial element for organisations to grow, survive and compete. Throughout decades, extensive research has disclosed many favourable and unfavourable predictors of creativity that can help managers and organisation promote creativity in the workplace. However, the complexity of creativity in the fast-paced competitive environment where multiple factors are likely at play, and their combined influences towards creativity, are not well understood. This thesis aims to focus on the complex and combined influence of positive and negative predictors of creativity through diverse methodologies; making theoretical and empirical contributions. This is a thesis by manuscripts. Thus, the majority of the chapters, though related, are stand-alone papers. These papers are published, under review, or final manuscripts submitted to targeted journals, as indicated at the start of each chapter. Chapters 1 and 2 introduce the rationale, detail a literature review of key predictors of creativity and associated theoretical approaches to understand relationships. From this review, broad research questions are developed that bind all papers of the thesis. Chapter 3 briefly explains the methodology of the six separate papers. Paper 1 (Chapter 4), a mapping review based on reviews dated 2014-2019, details the previous body of literature, its findings, and contributions, resulting in categorisation of predictors of creativity and innovation in themes: Psychological, Organisational, and Work (POW). This review proposes an integrative framework that helps shape a future research agenda for creativity and innovation research. Paper 1 also highlights looking at the influence of POW through the lens of Conservation of Resource (COR) theory (Hobfoll, 2001). Building on Paper 1, the influence of POW factors is explored on creativity behaviours in Papers 2-6 (Chapter 5-9) using COR theory, the resource caravan effect and crossover effects (Hobfoll, Halbesleben, Neveu, & Westman, 2018; Westman, 2001). Paper 2 and 3 focus on the combined influence of positive factors, and Papers 4 and 5 test the potential positive influence of negative factors (around stress) towards creativity when combined with positive factors. Theoretically, this tests the potential that negative resources can lead to positive outcomes but only in the presence of sufficient positive resources, which I term as ‘resource reservoir’. Paper 6 looks at the influence of crossover of resources from individual to teams and highlight the resource caravan effect combined with the crossover effect to provide new insights into creativity. Throughout the empirical papers, mediation, moderation and moderated mediations are tested and supported. Overall, this thesis contributes to the literature by providing an integrative review which is then empirically tested. Findings based on five diverse samples, predominately from New Zealand, using various methodologies including repeat-measures and multi-level designs, provide robust evidence around the combined influence of POW factors on creativity behaviour. Under COR, this thesis contributes to understanding how various positive and negative POW factors work in combination, and ultimately positively influence creativity at the individual-level and team-level. These findings have strong theoretical implications, including testing much of the COR theory assertions around testing multiple resources simultaneously, and managerial implications around the promotion of these resources.
Keywords: Creativity; Innovation; Psychological; Organisational; Work; Stress; Moderated mediation; Multi-level; Conservation of resources